A Conceptual Framework for Competency-based Web Intelligent Learning - R. M., Halim; C. S., Lee (2008)
A competency-based web intelligent system (CBWIS) enables learning to be more motivating with the provision of interactive and friendly user interfaces, communication networks, hypermedia databases, knowledgebase, and case material in novel and engaging ways. Furthermore, students can learn at their own pace, receiving individual attention and immediate feedback. This paper introduces a framework to develop a competency-based web intelligent system. The developed system will be intelligent enough in terms of providing hints or feedback. Throughout this system student's current knowledge about the subject is stored in a student model database and therefore materials are presented according to the student's learning needs.